Elementos humboldtianos en las teorías de la religión y de la magia de Konrad Th. Preuss - Paulina Alcocer (Journal de la Société des Américanistes)
On the affinities between Humboldt’s philosophy of language and Konrad Th. Preuss’ theories of magic and religion. This article deals with the affinities between the theory of magic and religion proposed by the German ethnologist Konrad Th. Preuss and Wilhelm von Humboldt’s philosophy of language. Through a comparative exposition of their methods for the analysis of the « intellectual culture », Preuss’ theories are supplemented with a philosophical grounding. The relation between their thought is established through the analysis of Preussian concepts such as « magic-religious way of thinking » and « complex representations » and Humboldt’s notions of the word-formation process, and the role of language and discourse in the constitution of a worldview.